Professional identity in students of the sixth year of human medicine at a public university, 2013 - Márquez Cabezas, Carlos Otildo (2018)
Introduction. Identity in students configures their self-recognition with the profession and involves the personal, family, cognitive, institutional and sociocultural. Objective. Know the components of the construction of the professional identity and the main phenomena that interact in said construction, in students of human medicine of the National University of San Marcos. Methods. A quantitative and qualitative study was carried out. 136 students from the sixth year of study participated in the study and were given a professional identity questionnaire. Sixteen students underwent an open interview. The processing of the data was done with the JMP V7 Software. Results. Of the 136 students evaluated, 63.2% had a favorable opinion regarding professional identity; 34.6%, intermediate; and 2.2%, unfavorable. From the qualitative analysis it was found that the early identification with the profession, the support provided by the family, as well as the affective, social and economic support, were present components in the students interviewed. Conclusions. The professional identity in sixth-year students of human medicine was mostly favorable. The construction of the professional identity had as components to the early identification with the profession, the family, and the affective, social and economic support.